Evaluation of an innovative, evidence‐guided, PBL approach. (5th May 2017) - Neve, Hilary; Bull, Stephanie; Lloyd, Helen; Gilbert, Kerry; Mattick, Karen
Summary: Aim: To understand the experiences of students and problem‐based learning (PBL) facilitators during an evidence‐based curriculum change to a PBL programme within an undergraduate medical course in South West England. Methods: Four novel PBL cases were designed and implemented, based on educational theory and evidence. Eight focus groups were undertaken with Year‐1 and ‐2 students ( n = 18) and PBL facilitators ( n = 14) to explore the experiences of participants. Thematic analysis and conceptual abstraction led to insights into the intended and unintended consequences of the change. Results: Participant responses to the change process were influenced by the perceived relevance and value of the change (e.g. benefit to student learning), which was shaped by individual beliefs and preferences (e.g. presumed purpose of PBL, relative value placed on different curriculum topics, and desire for uniform educational experience), and the wider education context (e.g. expectations of assessment). It appears that the three distinct elements must align for the changes to be received positively. We updated our PBL curriculum in response to new evidence Discussion: This study describes how we updated our PBL curriculum in response to new evidence, and demonstrates the importance of communicating the pedagogic rationale behind changes, and meticulous planning, preparation and alignment, even in distant parts of the curriculum. Engaging with existing views and attitudes is an essential requirement for successful curriculum change.